Olive oil Ameliorates renal Ischemia-reperfusion-mediated hepatic and renal changes in stressed rats - Noha S. Sobhy; Mona A. Ahmed; Noha N. Lasheen; Walaa Baher; Mohamed H. ElSayed (World Scientific Publishing, 2024)
Background: Renal ischemia-reperfusion injury (IRI) does not only affect kidneys, but also affects remote organs especially the liver. Stress may lead to further progression of renal and hepatic insults. This study was planned to explore the efficacy of olive oil (OO) on the assumed renal and hepatic changes of immobilization stress following renal IRI. Methods: Seventy-seven adult male Wistar albino rats were divided into the following five groups; Sham-Operated Control group, Renal Ischemia-Reperfusion group, Stressed Renal Ischemia-Reperfusion group, OO-Supplemented Renal Ischemia-Reperfusion group) and OO-Supplemented Stressed Renal Ischemia-Reperfusion Group (OO+Stressed+IR). All animals were subjected to determination of renal and hepatic biochemical functions and histopathological examination. Results: Renal IR significantly increased plasma creatinine and urea levels. This was associated with significant rise in serum levels of both ALT and AST, total bilirubin together with plasma level of TNF-[Formula: see text], whereas the plasma level of albumin (ALB) was significantly reduced. In addition, histological disruptions of kidneys and livers were observed. Chronic immobilization stress aggravated the effects of renal IR. Also, renal and hepatic morphological changes were more worsened. Whilst, OO supplementation resulted in significant amelioration of renal and hepatic functions. Also, the kidney and liver morphologic lesions were attenuated. Conclusion: Renal IR not only affected the renal functional and structural integrity but also the remote organ, the liver. Chronic immobilization stress rendered the kidney and liver more prone to injury. OO improved renal and hepatic dysfunction and morphological damage mediated by renal IRI, in control rats and in those exposed to chronic stress which can be exerted partially via its antioxidant, anti- inflammatory and nitric oxide (NO) reducing activities.